2020
DOI: 10.1126/scisignal.aay1451
|View full text |Cite
|
Sign up to set email alerts
|

High-throughput dynamic BH3 profiling may quickly and accurately predict effective therapies in solid tumors

Abstract: Despite decades of effort, the sensitivity of patient tumors to individual drugs is often not predictable on the basis of molecular markers alone. Therefore, unbiased, high-throughput approaches to match patient tumors to effective drugs, without requiring a priori molecular hypotheses, are critically needed. Here, we improved upon a method that we previously reported and developed called high-throughput dynamic BH3 profiling (HT-DBP). HT-DBP is a microscopy-based, single-cell resolution assay that enables che… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
52
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3
1

Relationship

2
8

Authors

Journals

citations
Cited by 48 publications
(52 citation statements)
references
References 39 publications
0
52
0
Order By: Relevance
“…Early time point mitochondrial apoptotic signaling predicts treatment responses Dynamic BH3 profiling (DBP) [21,22] was performed on PDX-derived tumor cells corresponding to HCI-010 ( Fig. 5a) and HCI-025 ( Fig.…”
Section: Navitoclax Enhances the In Vivo Efficacy Of Abt-414 Or Abbv-321mentioning
confidence: 99%
“…Early time point mitochondrial apoptotic signaling predicts treatment responses Dynamic BH3 profiling (DBP) [21,22] was performed on PDX-derived tumor cells corresponding to HCI-010 ( Fig. 5a) and HCI-025 ( Fig.…”
Section: Navitoclax Enhances the In Vivo Efficacy Of Abt-414 Or Abbv-321mentioning
confidence: 99%
“…These cell line-specific results highlight an important lesson for the use of alpelisib and BH3 mimetics in the clinical setting of breast cancer: fully taking advantage of this drug combination will require determining the relevant anti-apoptotic BCL-2 family dependence in the tumor. This could be accomplished by directly quantifying these BCL-2 family members in the tumor and/or by using functional genomic approaches such as dynamic BH3 profiling (Montero et al 2015;Montero et al 2019;Bhola et al 2020). In line with this view, recent clinical trials on breast cancer tumors with high BCL-2 expression have shown promising results with the combination of approved breast cancer therapies with the BCL-2 inhibitor venetoclax (Whittle et al 2020;Lok et al 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Our present results demonstrated that tamoxifen, fulvestrant and anastrozole were effective against breast cancer cells regardless of ER-α and ER-β expression status, even if the mechanism of action is different for each endocrine therapy agent. BH3 pro ling and dynamic BH3 pro ling have been e ciently used to determine anti-apoptotic BCL-2 protein dependency and to predict therapy response in hematologic malignancies and solid tumors 15,16,24,25 . Even though baseline mitochondrial priming by means of BH3 pro ling failed to provide an e cacious prediction for endocrine therapy response, dynamic BH3 pro ling was more effective.…”
Section: Discussionmentioning
confidence: 99%